Strategi Pemberdayaan Untuk Meningkatkan Partisipasi Civitas Akademika Dalam Penerapan Kampus Hijau Di Universitas Muhammadiyah Riau (UMRI) - Bakaruddin Bakaruddin; Norra Isnasia Rahayu; Jeki Algusri (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
The purposes of this study were to analyzed;1. Society of academicians empowerment, 2. Society of academicians participation on green campus implementation, and 3. Formulated of green campus strategy based on empowerment and society of academicians participation. This study is the mixed method, and sequential approach research. The results of this study was;1. Society of academicians participation was low category, 2. Society of academicians Empowerment was inappropriate category, and 3. Empowerment strategy based on society academicians participation was development of management system and society academicians empowerment capacity on green campus implementaion.